2016
DOI: 10.1063/1.4954683
|View full text |Cite
|
Sign up to set email alerts
|

Lithium concentration dependent structure and mechanics of amorphous silicon

Abstract: Theoretical prediction of fracture conditions for delithiation in silicon anode of lithium ion battery APL Materials 5, 106101 (2017);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…Corresponding to full lithiation, however, further reduction in elastic modulus and hardness is only 13% and 4%, respectively. As identied in our previous molecular dynamic simulations, 29 the initial breakdown of Si-Si bonds takes place up to the formation of Li 2.5 Si, followed by relatively slower bond breaking to form Li 3.75 Si. We believe these structural changes are responsible for the evolution of elastic modulus and hardness observed.…”
Section: Structure and Properties Of Lithiated A-si Thin Lmssupporting
confidence: 70%
See 2 more Smart Citations
“…Corresponding to full lithiation, however, further reduction in elastic modulus and hardness is only 13% and 4%, respectively. As identied in our previous molecular dynamic simulations, 29 the initial breakdown of Si-Si bonds takes place up to the formation of Li 2.5 Si, followed by relatively slower bond breaking to form Li 3.75 Si. We believe these structural changes are responsible for the evolution of elastic modulus and hardness observed.…”
Section: Structure and Properties Of Lithiated A-si Thin Lmssupporting
confidence: 70%
“…5a. With the Si-Si bond breaking and Si-Li bond formation, the structure becomes In our previous work, 29 we showed that the breakdown of Si-Si bonds dominantly takes place up to formation of Li 2.5 Si. At Li 2.5 Si, the silicon atoms are formed into isolated Si anions, Si-Si dumbbells and small clusters consisting with few Si atoms.…”
Section: Structure and Properties Of Lithiated A-si Thin Lmsmentioning
confidence: 94%
See 1 more Smart Citation
“…The spontaneous insertion of lithium ions into crystalline silicon anodes causes the formation of various amorphous phases of lithiated silicon (a-Li x Si). Because the energy barrier for lithium diffusion has been demonstrated to be dependent on the lithium concentration, with a lower energy barrier leading to faster lithium diffusion, the mobility of lithium tends to increase with increasing lithium concentration in silicon as demonstrated by ab initio MD simulations , and galvanostatic intermittent titration technique (GITT) results . On the basis of the free energy function of the regulation solution model, f = Ω c (1 – c ) + [ c ln c + (1 – c ) ln (1 – c )], the diffusivity, D = D o c d 2 f /d c 2 , can be described as D = D o [1/(1 – c ) – 2 Ω c ], where D o is the diffusion constant under stress-free conditions .…”
Section: Computational Methodsmentioning
confidence: 99%
“…This transformation is critical, as cracking in the Si anode generally occurs during delithiation under tension forces, confirmed by our previous experiments and molecular dynamics simulations. 27,28 The flexible liquid galinstan can alleviate the stress in tension and provide a self-healing function which prevents the cracking in the Si layer and delamination of the anode from the Cu current collector. In addition, the interfacial interactions between Cu/Si and galinstan/Si were investigated using a density functional theory (DFT) method (details of DFT simulations are in the Supporting Information).…”
mentioning
confidence: 99%